Effect of interaction energies on the adsorption of glycine onto a Cu(110) surface: A monte carlo simulation - Uñac, Rodolfo Omar (2009)
The purpose of the present work was to study the effect of the adsorbate-adsorbate interaction energy for the glycine/Cu(110) system using a Monte Carlo simulation in the grand canonical ensemble. The dependence of the surface pattern structures upon the temperature and diffusion rate was studied. For either reversible or irreversible adsorption, the results showed that it is possible to obtain condensed phases with a large degree of correlation for high diffusion rates and temperatures. Depending on the set of interaction energies for nearest-and next-nearest-neighbour molecules, these patterns form either hetero-or homo-chiral footprint domains.The results obtained are qualitatively consistent with the experimental pattern observed by other authors and allow an interpretation of the different proposed theoretical models used to explain experimental data.